الإقامة المستحدثة في ريف اللاذقية (السكن المتناوب بين القرية والمدينة) - عقيل, أديب; دياب, أمين (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
أكدت النظرية الاجتماعية على التأثير المتبادل بين التجمعات البشرية ومواقعها الطبيعية , وإن حال السكن المتناوب يدعو للتساؤل عن طبيعته بين أنماط التجمعات البشرية المعروفة . فتم اعتماد بحث اجتماعي ميداني أعطى النتائج التالية: يحوي السكن المتناوب أسراً ريفية , عاد قسم منها إلى القرية بعد هجرة فردية أو جماعية, وقسم آخر منها انتقل مباشرة من القرية إلى المدينة, وسكنوا جميعاً في مسكنين بالتناوب (في القرية والمدينة). بدأ قيام هذا السكن عام 1970 وتكرر حتى عام 2010 م, وظهر إقامة مستحدثة , كما ظهرت أحوال هذا السكن الاقتصادية والاجتماعية والتعليمية ... الخ , بأنها معطيات تحقق أهداف الهجرة من القرية والعودة إليها. تلاقت قيم القرية مع قيم المدينة في هذا السكن , فزاد عندها تحضر القرية وترييف المدينة. The social theory has emphasized the mutual effect between the human communities and their natural areas. The case of alternative residence creates an inquiry about its nature among the styles of the common human communities. Therefore, a social field research is depended and gave the following results: The alternative residence has rural families, some of them have returned to the village after individual- or group-migration, and others that have moved immediately from the village to the city, and all of them live in two residences alternately ( in the village and the city). This residence has begun since 1970 and repeated till 2010, and finally appeared as an innovative stay. The economic, social, educational cases of this residence have also appeared as conditions that attainthe goals of migration from the village and going back to it again. The values of both village and city have met in this residence, so, the urbanization of village and the ruralization of city have increased.